Generation of OAM Beam with High Azimuthal Symmentry through Planar UCA for Vehicular Communication - Mallikharjuna Reddy, Y.; Ratna Kumari, U. V. (Advanced Electromagnetics, 2023)
In this paper, a uniform circular array (UCA) with circularly polarized (CP) square patches is presented for the generation of orbital angular momentum (OAM) beam with high azimuthal symmetry. The proposed CP UCA is a compact structure with a simple feed network generating OAM beams. The design consists of eight circularly polarized square patch antennas which are geometrically rotated to obtain the required phase distribution. The left hand circularly polarized square patch used as a radiating element in UCA exhibits l = + 1 OAM mode, while the right hand circularly polarized square patch exhibits l = - 1 OAM mode. In addition, the antenna exhibits a single-layer structure, which facilitated the fabrication of the design and reduced the cost as well. The simulated and measured results are reported showing that the antenna exhibits an OAM beam of l = + 1 and l = - 1 modes at 5.85 GHz with high azimuthal symmetry. The mode purity estimation is also reported for the OAM l = + 1 and l = - 1 modes. The gain of the conical shaped OAM beam is almost 11 dBi which makes it quite viable for applications in wireless and vehicular communications.